Tasawuf Nusantara: Wuṣūl Perspektif Mbah Munshorif Dalam Al-Bidayat Majallatun Nihayat - M. Alan Al Farisi (Hikamia: Jurnal Pemikiran Tasawuf dan Peradaban Islam, 2024)
Abstract This research is motivated by the oddity of Mbah Munshorif and his book. Mbah Munshorif is not an educated person but has an extraordinary book containing Sufism lessons, one of which explains about wuṣūl to Allah. To find out the figure of Mbah Munshorif and his concept of wuṣūl to Allah, the author then conducted a research with the title "Tasawuf Nusantara: The Concept of Wuṣūl from the Perspective of Mbah Munshorif in the Book of Al-Bidayat Majallatun Nihayat" with a qualitative research method that uses interviews and analysis of Mbah Munshorif's documents. From the research that has been done, it can be seen that Mbah Munshorif is a community leader who has the uniqueness of having many students from various regions, some of whom are educated and educated people, even pesantren caretakers and lecturers. Even though he never received a higher education. In addition, Mbah Munshorif is famous for his various miracles, one of which is folding the earth. Mbah Munshorif has a concept of tasaswuf or wuṣūl which has a tendency to tawakal. Mbah Munshorif said that wuṣūl is solely a gift from Allah. If a person is wuṣūl to Allah, Allah will cover all his shortcomings and defects with His majesty, greatness, glory, and versatility. Thus, the person is overwhelmed by His noble attributes and His supreme will until his ego and all his desires are gone. Keywords: Mbah Munshorif, Tawakal, Wuṣūl. Abstrak Penelitian ini dilatarbelakangi keganjilan Mbah Munshorif dan bukunya. Di mana Mbah Munshorif bukanlah orang terpelajar namun memliki buku yang lauar biasa yang berisikan pelajaran tasawuf yang salah satu isinya menjelaskan mengenai wuṣūl kepada Allah. Untuk mengetahui sosok Mbah Munshorif dan konsep wuṣūl-nya kepada Allah, penulis kemudian melakukan penelitian dengan judul “Tasawuf Nusantara: Konsep Wuṣūl Perspektif Mbah Munshorif dalam kitab Al-Bidayat Majallatun Nihayat” dengan metode penelitian kualitatif yang menggunakan wawancara dan analisis dokemen karya Mbah Munshorif. Dari penenlitian yang telah dilakukan dapat diketahui bahwa Mbah Munshorif merupakan tokoh masyarakat yang mempunyai keunikan memmiliki banyak murid dari berbagai daerah yang sebagainnya adalah orang-orang terpelajar dan terdidik, bahakan pengasuh pesantren dan dosen. Padahal beliau tidak pernah mengenyam pendidikan yang tinggi. Selain itu, Mbah Munshorif terkenal dengan berbagai karamah-nya yang salah satunya adalah melipat bumi. Mbah Munshorif mempunyai konsep tasawuf atau wuṣūl yang mempunyai kecenderungan pada tawakal. Mbah Munshorif mengatakan bahwa wuṣūl merupakan semata-mata anugerah Allah. Baranag siapa yang dikehendaki Allah wuṣūl kepada-Nya, maka Allah akan menutupi segala kekurangan dan kecacatannya dengan keagungan, kebesaran, kemuliaan, dan kesempunaan-Nya. Sehingga orang tersebut diliputi segala sifat-Nya yang mulia dan kehendaknya yang paling kuasa hinga sirnalah egonya dan segala kehendaknya adalah kehendak Allah serta pilihannya adalah pilihan Allah.